Finite-State Spell-Checking with Weighted Language and Error Models : Building and Evaluating Spell-Checkers with Wikipedia as Corpus - Pirinen, Tommi; Linden, Krister (2012)
In this paper we present simple methods for construction and evaluation of finite-state spell-checking tools using an existing finite-state lexical automaton, freely available finite-state tools and Internet corpora acquired from projects such as Wikipedia. As an example, we use a freely available open-source implementation of Finnish morphology, made with traditional finite-state morphology tools, and demonstrate rapid building of Northern Sámi and English spell checkers from tools and resources available from the Internet. Peer reviewed